Information technology: The management challenge - N Caroline Daniels (Addison-Wesley, 1994)
The book balances theory and proven management frameworks and is illustrated with practical cases; explains in management terms the capabilities of IT in business; provides a good guide to discover how to apply IT for strategic advantage